THE BUSINESS ANALYSIS OF TILAPIA RED FISH (Oreochromis sp) CULTURE IN PONDS (TAMBAK) AT TELUK PAPAL VILLAGE BANTAN SUBDISTRICT BENGKALIS REGENCY RIAU PROVINCE - Tengku Hara Marsyitah; Lamun Bathara; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted on April 2016 on Balai Benih Ikan Pantai at Teluk Papal village Bantan subdistrict Bengkalis Regency Riau Province. The method used in this study by case study method . The respondents in this research are 3 person, there are 1 manager and 2 farmers. Based on research result that the Business of Tilapia fish (Oreochromis niloticus) culture in ponds at Teluk Papal village have some conclusion, that is cost incurred for the culture of Tilapia it’s the fixed cost and variable cost. The fixed cost the issued to all compenents it’s of Rp. 11.010.000 with the depreciation of cost it’s of Rp. 517.000. For the variable cost components it’s of Rp. 42.432.000. This business get advantage or net income it’s of Rp. 14.651.000 per harvest. This business of Tilapia fish (Oreochromis niloticus) farming in ponds declared unfit to continue. Because, provided the value of RCR > 1 with getting value it’s of 1,34. The times is needed for restore capital it’s for 3 years 6 months. Keywords :The Business Analysis, Farming of Tilapia Red Fish (Oreochromis sp)